Pelestarian Tanaman Obat Di Kampung Inggembai Pegunungan Arfak Papua Barat - Rini Maryone (Universitas Cenderawasih, 2022)
The condition of the natural environment of the Arfak Mountains which has the potential for abundant flora diversity makes people in the Arfak Mountains specifically in Iggembai Village to use these plants as medicinal plants/traditional medicines. Based on this, the problems formulated are How do the people in Iggembai Village, Anggi Gida District use plants as ingredients for traditional medicine, How to use and process plants used as community medicine in Iggembai Village, Anggi Gida District for traditional medicine and How to preserve medicinal plants in life community in Iggembai Village, Anggi Gida District. To answer the problems mentioned above, the authors use an exploratory survey method with data collection techniques through direct observation and interviews with key figures, as well as users of medicinal plants in the research location. The results obtained data on the diversity of various types of medicinal plants as many as 23 species. Inventory and documentation of medicinal plants and their traditional knowledge need to be continued for the benefit of knowledge and conservation as well as the welfare of the people who own the knowledge. Scientific evidence based on existing empirical evidence should also continue to be improved.